2009
DOI: 10.1111/j.1399-5618.2009.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

The International Society for Bipolar Disorders (ISBD) Task Force report on the nomenclature of course and outcome in bipolar disorders

Abstract: Determination and dissemination of a consensus nomenclature serve as the first step toward producing a validated and standardized system to define course and outcome in bipolar disorders in order to identify predictors of outcome and effects of treatment. The task force acknowledges that there is limited validity to the proposed terms, as for the most part they represent a consensus opinion. These definitions need to be validated in existing databases and in future studies, and the primary goals of the task fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
320
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(341 citation statements)
references
References 86 publications
(129 reference statements)
6
320
0
11
Order By: Relevance
“…23 While the construct of "recovery" from episodes of mood disorder has often been defined based mainly, if not solely, on the basis of affective symptom resolution sustained for at least 8 weeks, 21,28 a more rigorous definition of "recovery" that incorporates the absence of functional impairment was proposed over 30 years ago in the Research Diagnostic Criteria. 29 However, rigorous definitions of "recovery" that incorporate both symptomatic remission and functional improvement as indicators of treatment success have been used in only a handful of outcome studies (e.g., the National Institute of Mental Health Collaborative Depression Study) by Solomon et al 30 and Loebel et al 23 Judd et al 31 proposed a definition of major depressive episode recovery as an 8-week period free of all symptoms associated with the previous major depressive episode (asymptomatic recovery).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23 While the construct of "recovery" from episodes of mood disorder has often been defined based mainly, if not solely, on the basis of affective symptom resolution sustained for at least 8 weeks, 21,28 a more rigorous definition of "recovery" that incorporates the absence of functional impairment was proposed over 30 years ago in the Research Diagnostic Criteria. 29 However, rigorous definitions of "recovery" that incorporate both symptomatic remission and functional improvement as indicators of treatment success have been used in only a handful of outcome studies (e.g., the National Institute of Mental Health Collaborative Depression Study) by Solomon et al 30 and Loebel et al 23 Judd et al 31 proposed a definition of major depressive episode recovery as an 8-week period free of all symptoms associated with the previous major depressive episode (asymptomatic recovery).…”
Section: Discussionmentioning
confidence: 99%
“…While both symptomatic and functional improvement are important components of full recovery, 21,23,[35][36][37][38][39][40] and may be linked, as demonstrated in several studies, 23,[35][36][37][38] they are not necessarily always coincident. 21,23,[35][36][37][40][41][42][43] The observation that functional recovery often lags behind symptomatic or syndromal recovery 41 may account for this lack of coincidence in the components of recovery.…”
Section: Madrs <= 12 Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The International Society for Bipolar Disorders (ISBD) Task Force has reported that the most commonly used definition of remission in bipolar mania is a YMRS score < 12; remission has been further operationalised as a CGI‐Bipolar Disorder Scale severity score ≤ 2 (borderline ill) for both mania and depression 14. In our post hoc category shift analyses, significantly more cariprazine‐treated patients than placebo‐treated patients with bipolar disorder shifted to borderline ill (CGI‐S = 2) or normal (CGI‐S = 1), which would suggest that these patients reached symptomatic remission with treatment.…”
Section: Discussionmentioning
confidence: 99%